Catalytic Enantio‐ and Diastereoselective Mannich Addition of TosMIC to Ketimines1. Issue 67 (31st October 2018) - Franchino, Allegra; Chapman, Jack; Funes‐Ardoiz, Ignacio; Paton, Robert S.; Dixon, Darren J.
Abstract: Chiral amines bearing a stereocenter in the α position are ubiquitous compounds with many applications in the pharmaceutical and agrochemical sectors, as well as in catalysis. Catalytic asymmetric Mannich additions represent a valuable method to access such compounds in enantioenriched form. This work reports the first enantio‐ and diastereoselective addition of commercially available p ‐toluenesulfonylmethyl isocyanide (TosMIC) to ketimines, affording 2‐imidazolines bearing two contiguous stereocenters, one of which is fully‐substituted, with high yields and excellent stereocontrol. The reaction, catalyzed by silver oxide and a dihydroquinine‐derived N, P‐ligand, is broad in scope, operationally simple, and scalable. Derivatization of the products provides enantioenriched vicinal diamines, precursors to NHC ligands and sp 3 ‐rich heterocyclic scaffolds. Computations are used to understand catalysis and rationalize stereoselectivity. Abstract : The first enantio‐ and diastereoselective addition of p ‐toluenesulfonylmethyl isocyanide (TosMIC) to (hetero)aromatic and aliphatic ketimines provides imidazolines with two contiguous stereocenters, which can be elaborated to vicinal diamines, precursors to NHC ligands and sp 3 ‐rich heterocyclic scaffolds. Computations made it possible to rationalize the stereochemical outcome in reactions catalyzed by silver(I) and a dihydroquinine‐derived N, P‐ligand.